Antibacterial electro-explosive Co/CoO composite nanoparticles: Synthesis, structure, magnetic and antibacterial properties - Lozhkomoev, Aleksandr S.; Bakina, Olga V.; Kazantsev, Sergey O.; Glazkova, Elena A.; Rodkevich, Nikolay G.; Lerner, Marat I. (Journal of magnetism and magnetic materials)
Composite Co/CoO nanoparticles have been obtained by the method of electrical explosion of wires (EEW) in mixed argon/oxygen gas medium. The influence of the O2 content in the gas medium on the composition and characteristics of the EEW products was studied. The morphology and dimensional characteristics of Co/CoO nanoparticles were studied by transmission electron microscopy. The crystal structure of the nanoparticles has been found to be represented by phases corresponding to Co and CoO, and the average particle size being about 60 nm. As the O2 content in the gas medium increases from 1 to 3.5 vol%, the CoO content increases from 20 to 70 wt%). The magnetization of the samples decreases from 89.6 to 25.6 emu/g with increasing CoO content. The antibacterial activity of the samples against methicillin-resistant S.aureus (MRSA) reached 86 % reduction in the number of bacteria for the nanoparticles with the highest CoO content. The findings demonstrate the potential application of composite nanoparticles as promising antibacterial agents against resistant strains